1) Given y = x+2 and y = -4x-8.
Since the left hand sides of both equations are same, equate the right hand side of both the equations.
![x+2=-4x-8](https://img.qammunity.org/2023/formulas/mathematics/college/lhvfsn5n8mzjyzci91cglt78oylgxr45ob.png)
Add 4x on both sides.
![\begin{gathered} x+2+4x=-4x-8+4x \\ 5x+2=-8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zbu6z9ycopx7efiibw2bdkatoqjyshrfd6.png)
Add -2 on both sides.
![\begin{gathered} 5x+2-2=-8-2 \\ 5x=-10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4cgptgfmuze6maade769f2hd8zadlfo0lf.png)
Divide by 5 on both sides.
![\begin{gathered} x=-(10)/(5) \\ =-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zl5xo3xpqp25t5n9scuuh6cm8k5v39d65d.png)
Substitute the value of x into y = x+2.
![\begin{gathered} y=-2+2 \\ =0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/esgkn3zxo3r1o5ci03fz0gg21xfx4dr2ow.png)
Solution is (-2,0).
2) Given y = 3x+1 and y = -2x+6.
Since the left hand sides of both equations are same, equate the right hand side of both the equations.
![3x+1=-2x+6](https://img.qammunity.org/2023/formulas/mathematics/college/tf3d8dtfwwmy0ate7mkpt8df3r2fz13brh.png)
Add 2x on both sides.
![\begin{gathered} 3x+1+2x=-2x+6+2x \\ 5x+1=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2bhwngeu233u59hgx0pfmqs8emcn8ae4oj.png)
Add -1 on both sides.
![\begin{gathered} 5x+1-1=6-1 \\ 5x=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ysb5889cx799ig03je41av3u283bcf7pyn.png)
Divide by 5 on both sides.
![\begin{gathered} x=(5)/(5) \\ =1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u06d75k8mapao2v867zgngtq60e51iqicf.png)
Substitute the value of x into y = 3x+1.
![\begin{gathered} y=3\cdot1+1 \\ =4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uwmb9samu9i5cazy9wgczbe5tkunqtrxsi.png)
Solution is (1, 4).
3) Given y = -3x-6 and 6x+2y = -2.
Substitute -3x-6 for y into 6x+2y = -2.
![\begin{gathered} 6x+2(-3x-6)=-2 \\ 6x-6x-12=-2 \\ -12=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xasmmn389bnjuq58hxhu804rlvfd2t030z.png)
which is not possible. Hence the given system of equations has no solution.
4) Given y = -5 and -8x+4=-20.
From the second equation, -8x+4 = -20, solve for x.
Add -4 on both sides.
![\begin{gathered} -8x+4-4=-20-4 \\ -8x=-24 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qaj4stmkj9wqmig4r3fa4c0xed3zejds2a.png)
Divide by -8 on both sides.
![\begin{gathered} x=(-24)/(-8) \\ =3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/axr9lvwzazi7rcwpb2zm7iagp262tpb1oe.png)
Solution is (-5, 3).